Kebijakan Hukum Dalam Menangani Kasus Bullying Pada Pelanggaran Hak Azasi Manusia Di Lingkungan Sekolah - Aziz, Hasnah; Hafidati, Putri (Lex Jurnalica, 2024)
Abstract Looking at various news and several media, we can find out that bullying cases are still rampant, especially in the school environment and most of the victims are minors. This study aims to analyze human rights violation policies in handling bullying cases. Methods This research uses normative juridical methods. However, until now bullying is still considered a trivial thing, even though it needs special attention from related parties that bullying is a form of violation of Human Rights (HAM) that cannot be underestimated. Human rights themselves are various, including the right to a proper education. In order for human rights in Indonesia to run as they should, that's where a protection of human rights emerges, especially in the field of education. With the protection of human rights in the field of education, so that there are no violations of human rights in the field of education, such as the emergence of bullying incidents in schools, where the bullying incident has a very negative impact. Among the negative impacts of the bullying incident is that it can cause violence, both verbal and physical violence. Keywords: Human Rights, Education, Bullying  Abstrak. Melihat dari berbagai berita dan beberapa media kita dapat mengetahui bahwa kasus bullying masih marak terjadi terutama di lingkungan sekolah dan kebanyakan korban adalah anak dibawah umur. Penelitian ini bertujuan untuk meganalisis kebijakan pe.langgaran Hak Asasi Manusia dalam pe.nanganan kasus Bullying. Me.tode. Pe.ne.litian ini me.nggunakan me.tode. yuridis normatif.  Namun, hingga saat ini bullying masih di anggap suatu hal yang se.pe.le.h, padahal pe.rlu pe.rhatian khusus dari pihak yang te.rkait bahwa bullying adalah be.ntuk tindakan pe.langgaran Hak Asasi Manusia (HAM) yang tidak bisa dianggap re.me.h. Hak asasi manusia se.ndiri be.rmacam-macam diantaranya  yaitu hak untuk me.mpe.role.h pe.ndidikan yang layak. Agar hak asasi manusia di Indone.sia dapat be.rjalan se.bagaimana me.stinya, maka dari situlah muncul suatu pe.rlindungan hak asasi manusia khususnya dibidang pe.ndidikan. De.ngan adanya pe.rlindungan hak asasi manusia dibidang pe.ndidikan ini  supaya tidak adanya pe.langgaran hak asasi manusia dibidang pe.ndidikan, se.pe.rti munculnya pe.ristiwa bullying yang ada di se.kolah, dimana pe.ristiwa bullying te.rse.but me.mbawa dampak yang sangat ne.gatif. Diantara dampak ne.gatif dari adanya pe.ristiwa bullying te.rse.but yaitu dapat me.munculkan adanya ke.ke.rasan, baik ke.ke.rasan se.cara ve.rbal maupun se.cara fisik.  Kata Kunci : Hak Asasi Manusia, Pe.ndidikan, Bullying